Power distribution automation - Das, Biswarup (Electrical engineer) (IET power and energy series ;, 2016)
Utilities around the world are under increasing pressure to provide reliable and good quality power supply to their retail customers, and to reduce their operational costs. These concerns call for real time monitoring and control of the distribution system, which can be accomplished by deploying distribution automation (DA) systems, a key enabling technology for smart grids. This book provides a detailed description of all the major components of a DA system, including communication infrastructure and analysis tools. Topics covered include communication systems for distribution automation; load flow analysis; short circuit analysis; state estimation; feeder reconfiguration for loss reduction, service restoration, and load balancing; volt-var control; fault location; fault type identification; and economic analysis/cost benefit analysis. Concluding with an international case study (Enexis, one of the major Distribution System Operators in The Netherlands) showing how DA has been implemented in practice, this book is essential reading for researchers and advanced students working in power engineering and practitioners engaged in distribution automation, such as utility engineers, vendors, and consultants.